1992
DOI: 10.1192/bjp.160.6.788
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Environmental Temperature to the Incidence and Outcome of Schizophrenia

Abstract: This paper presents new analyses of data from two multicentre studies carried out by the WHO. The morbid risk of developing schizophrenia, as broadly defined by the Determinants of Outcome Study, was positively related to the mean daily range of temperature. The outcome of schizophrenia, as determined by the International Pilot Study of Schizophrenia, was found to be positively related to mean environmental temperature. Further studies are needed to examine the relationship of geographical and climatic variabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(25 citation statements)
references
References 33 publications
3
22
0
Order By: Relevance
“…In spite of the prime importance attached to them, psychological studies on the impact of thermal environment are still at their infancy (18, 38). According to Hensel (1981), thermo-reception resulting in qualities such as warmth is qualitative, originating as it does from sensory experience, and it therefore cannot be based on physics or physiology (37).…”
Section: Discussionmentioning
confidence: 99%
“…In spite of the prime importance attached to them, psychological studies on the impact of thermal environment are still at their infancy (18, 38). According to Hensel (1981), thermo-reception resulting in qualities such as warmth is qualitative, originating as it does from sensory experience, and it therefore cannot be based on physics or physiology (37).…”
Section: Discussionmentioning
confidence: 99%
“…The importance of these variables is well established for affective disorders (Myers & Davies, 1978;Mawson & Smith, 1981;Parker & Walter, 1982;Silverstone et al, 1995;Morken et al, 2002;Hakkarainen et al, 2003;Volpe & del Porte, 2006;Lee et al, 2007;Boker et al, 2008). Their role in schizophrenia is less extensively characterized, although a correlation between monthly admission rates and mean maximal monthly temperature has been found by some investigators (Gupta & Murray, 1992;Shiloh et al, 2005).…”
Section: Introductionmentioning
confidence: 98%
“…Only a few studies examined the relationship between DTR and schizophrenia admissions (Gupta and Murray, 1992;Sung et al, 2011), which limited us to directly compare the results with others. Early in 1992, Gupta and Murray reported a positive correlation between mean daily range of temperature and emergency admissions for schizophrenia.…”
Section: Discussionmentioning
confidence: 98%
“…However, to the best of our knowledge, there have been only two studies on DTR in relation to schizophrenia (Gupta and Murray, 1992;Sung et al, 2011). A recent study in Taiwan found that an increasing DTR may contribute to the emergency admission for schizophrenia, but the lagged effects of within-day variation in temperature have not been evaluated in detail.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation